2022
DOI: 10.1039/d1ra08220e
|View full text |Cite|
|
Sign up to set email alerts
|

Sulphonated graphene oxide catalyzed continuous flow synthesis of pyrazolo pyrimidinones, sildenafil and other PDE-5 inhibitors

Abstract: Sulphonated graphene oxide was used for cascade condensation and cyclization reactions towards accessing substituted pyrazolo pyrimidinones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Recently, our research group has reported an individual and integrated continuous multi-step reaction protocol for the on-demand synthesis of daclatasvir, 27 rosiglitazone, 28 pioglitazone, 28 sildenafil, 29 etc. In continuation of our efforts on flow synthesis, we postulated that a rational choice of reagent and solvent in conjunction with close control of reaction conditions such as pressure, temperature, stoichiometric ratio and reaction time, commenced by a continuous flow process, would allow us to take up the on-demand synthesis of DRV efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our research group has reported an individual and integrated continuous multi-step reaction protocol for the on-demand synthesis of daclatasvir, 27 rosiglitazone, 28 pioglitazone, 28 sildenafil, 29 etc. In continuation of our efforts on flow synthesis, we postulated that a rational choice of reagent and solvent in conjunction with close control of reaction conditions such as pressure, temperature, stoichiometric ratio and reaction time, commenced by a continuous flow process, would allow us to take up the on-demand synthesis of DRV efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] The results show that the electrochemical sensitivity is greatly enhanced by modifying rGO with sulfonic acid groups. 25,26 The introduction of additional asymmetricity through the incorporation of transition metal dichalcogenide (TMD) materials would augment the sensitivity of the composite material. MoS 2 is one such TMD that has riveted researchers over the past two decades due to its superior specific surface area, better porosity, and electronic conductivity as it allows shifting from a multi-layered network of indirect bandgap 1.29 eV to a single-layered network of direct bandgap 1.9 eV making it a principal choice amongst scientist for sensitive and rapid sensing applications.…”
Section: Introductionmentioning
confidence: 99%